Modelo de placenta humana para simulação de microcirurgia e ultrassonografia em tumores cerebrais - Audrey Beatriz Santos Araujo (2017)
Background: Brain tumors are complex 3-dimensional lesions. Their resection involves training and the use of the multiple microsurgical techniques available for removal. Simulation models, with haptic and visual realism, may be useful for improving the bimanual technical skills of neurosurgical residents and neurosurgeons, potentially decreasing surgical errors and thus improving patient outcomes. Objective: To describe and assess an ex vivo placental model for brain tumor microsurgery and interventional ultrasonography using a simulation tool in neurosurgical psychomotor teaching and assessment. Methods: Forty placentas were used in this research project. Intravascular blood remnants were removed by continuous saline solution irrigation of the 2 placental arteries and placental vein. Brain tumors were simulated using silicone injections in the placental stroma. Eight neurosurgeons and 8 neurosurgical residents carried out the resection of simulated tumors. Eight interventional radiologists and 30 neurosurgeons performed interventional ultrasonography to evaluate deep cyst puncture. Face and content validity was assessed using a subjective evaluation based on a 5point Likert scale. Construct validity was assessed by analyzing the surgical performance of the neurosurgeons, residents and radiologists groups. Results: The placenta model simulated brain tumor surgical procedures with high fidelity. Results showed face and content validity. Construct validity was demonstrated by statistically different surgical performances among the evaluated groups. The placenta ex vivo hybrid simulator showed very good similarity with real scenarios (Face validity), with high fidelity of all part tasks (Content validity). Conclusion: Human placentas are useful haptic models to simulate brain tumor microsurgical removal and cystic puncture guided by ultrasonography. Results using this model demonstrate face, content, and construct validity.